Serial estimation of serum albumin and its role in traumatic brain injury patients - Pandey, Mithilesh Kumar; Baranwal, Sunil Kumar; Panwar, Deepak Singh; Saha, Suniti Kumar; Roy, Kaushik; Ghosh, Subhasis; Tripathy, Parimal (Asian Journal of Medical Sciences, 2016)
Background: Serum albumin is routinely measured; cheap and easily available test even in remote areas laboratories. Albumin is the major protein of human plasma and one of the negative acute phase reactants reported to fall as a component of metabolic response to injury or infection, independent of the nutritional status. Even though this has also been noted in patients with head injury and its overall significance with respect to neurological outcome following head injury are yet to be established. Aims and Objectives: To assess the role of serum albumin in outcome of head injury patient. Material and Methods: This is a prospective case control study. Total 200 cases of traumatic brain injury [152 male and 48 female] were studied in NRS Medical College, Kolkata from September 2012 to October 2013. Serum albumin estimation, along with clinical and radiological data was collected. Serum albumin was compared between among various subgroups and outcome was assessed by Glasgow Coma Scale at 6 months. Results: In present study 86(43%) patients having hypoalbuminemia (< 3.5gm/dl) and falling trend in admission serum albumin levels from day 1 to 10th day with decrement in GCS was statistically highly significant (p < 0.001) as hypoalbuminemia was noted in 68%, 39.65 and 33.43% patients with severe, moderate and mild head injury respectively. The present study was showed that female TBI patients having less no. of hypoalbuminemia compare to male as 77.7%, 45.4%, 31.4% male and 42.8%, 28.5%, 27.2% female having hypoalbuminemia (< 3.5gm/dl) in severe, moderate and mild head injury respectively and statistically significant difference in severe and moderate group. Conclusion: The serial estimation of serum albumin in traumatic brain injury patients provides the treating doctor an insight in the prognosis of the patient so that they can be managed aggressively. Asian Journal of Medical Sciences Vol.7(4) 2016 31-38